Chemical Profile Study and Screening in Silico of Cyclooxygenase-2 Inhibitor Chemical Compounds from Ethanol Extract Of Mangosteen Fruit Peel (Garcinia Mangostana L.) - Akbar, Harul; Najib, Ahmad; Fawwaz, Muammar (Indonesian Research Journal on Education, 2025)
Chemical profile studies and screening in silico of cyclooxygenase-2 inhibitor chemical compounds from ethanol extract of mangosteen fruit peel (Garcinia mangostana L.). The purpose of the study was to determine the profile of chemical compounds contained in ethanol extract of mangosteen fruit peel (Garcinia mangostana L.) which has the potential to be a cyclooxygenase-2 inhibitor by the screening method in silico. The extraction of mangosteen peel (Garcinia mangostana L.) was carried out by maceration method using 96% ethanol solvent for 3 days then filtered and thickened with a rotary vacuum evaporator. An extract with a yield value of 8% is produced. The resulting extract was tested using the GC-MS instrument under the following conditions; injector temperature 250°C, initial oven temperature 70°C, up to 325°C in 10°C/min increments. 100 chemical compounds were obtained and a 2D compound structure was created with ACD/ChemSketch. The cyclooxygenase-2 enzyme model was obtained through the Protein Data Bank (PDB) site with the code 1CX2. Optimization is carried out on chemical compounds with the Discovery Visual Studio program. The docking process was carried out on chemical compounds with cyclooxygenase-2 as the receptor target using the Vina method with the help of the Pyrx program. The value of free energy change (∆G) is evaluated as a result of docking. The docking results showed that the compound contained in the ethanol extract of mangosteen fruit peel (Garcinia mangostana L.) has the potential as an inhibitor of cyclooxygenase-2 in silico and the one that has the best free energy change (∆G) in silico is oleana-11,13(18)-diene with a free energy change (∆G) -12,500 kcal/mol.